2001
DOI: 10.1002/1097-0355(200101/04)22:1<7::aid-imhj2>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a secure attachment relationship on right brain development, affect regulation, and infant mental health

Abstract: Over the last ten years the basic knowledge of brain structure and function has vastly expanded, and its incorporation into the developmental sciences is now allowing for more complex and heuristic models of human infancy. In a continuation of this effort, in this two-part work I integrate current interdisciplinary data from attachment studies on dyadic affective communications, neuroscience on the early developing right brain, psychophysiology on stress systems, and psychiatry on psychopathogenesis to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
642
1
83

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 953 publications
(737 citation statements)
references
References 289 publications
(256 reference statements)
11
642
1
83
Order By: Relevance
“…Schore, 2001; Schore & Schore, 2008; Siegel, 2017). Seeking proximity to their caregiver is a common and coherent strategy in infants for regulating distress.…”
Section: Bowlby’s Theory: Self-regulation and Disorganizationmentioning
confidence: 99%
“…Schore, 2001; Schore & Schore, 2008; Siegel, 2017). Seeking proximity to their caregiver is a common and coherent strategy in infants for regulating distress.…”
Section: Bowlby’s Theory: Self-regulation and Disorganizationmentioning
confidence: 99%
“…The human newborn is born with a relatively small brain, but science has shown that it is perfectly wired and competent for early extra-uterine life (Schore 2001a;Winberg 2005). A human will never be as alert as after a vaginal birth: noradrenalin wakes up the brain and is 10 times higher at birth than ever again (Lagercrantz & Bistoletti 1977).…”
Section: Trendsmentioning
confidence: 99%
“…Previous research has identified a well-established link between attachment styles and developmental outcomes, including mental health, e.g. depression; physical health and social outcomes (Bifulco et al, 2004;Bowlby, 1980;Schore, 2001;Sroufe, 2005;Sroufe, Egeland, Carlson, & Collins, 2005a).…”
Section: Introductionmentioning
confidence: 99%